R&D intensity and firm performance of SME firms in Thailand: the moderating role of firm size - Muttanachai Suttipun; Krittiga Insee (Cogent Business & Management, 2024)
Unlike large firms, the relationship between research and development (R&D) intensity and the firm performance of small- and medium-enterprise firms (SME firms) was found that in the past many studies However, the results of the study of this relationship still differ according to the context, especially in Thailand. Therefore, this study aims to test whether there is a possible relationship between R&D intensity and firm performance, moderated by the size of SME in Thailand. A total of 151 Thai SME firms from The Office of National Higher Education Science Research and Innovation Policy Council were used as samples. The data were analyzed using questionnaires sent via mail, descriptive analysis, a correlation matrix and multiple regression. The results reveal that R&D intensity has a negative effect on firm performance, whereas firm size has a positive effect on firm performance. Additionally, the interaction effect between R&D intensity and firm size has a significant negative effect on firm performance. The study's findings might provide general investors and Thai SME enterprises with helpful guidelines for comparing business performance to R&D expenses. The Thai government can also benefit from this information when developing policies that support R&D in Thailand
Keywords: G30; M12; O31; 650; R&D intensity; firm performance; SMEs firm; Thailand